Forced Degradation Study Of Paracetamol Levels Using Uv-Vis Spechtrophotometry: Studi Degradasi Paksa Terhadap Kadar Paracetamol Menggunakan Spektrofotometri UV-Vis - M.A. Hanny Ferry Fernanda; Maulidia Ningsih (Akademi Farmasi Surabaya, 2023)
Paracetamol or acetaminophen is a class of over-the-counter drugs widely used by the general public to treat fever and mild pain. The study aimed to determine the effect of forced degradation by hydrolysis on paracetamol levels using Uv-Vis Spectrophotometry. This type of research is experimental with the method used is Uv-Vis Spectrophotometry which is carried out at a wavelength of 200-400 nm. The results obtained from the study in the form of a linear regression equation y=0,0652x + 0,0269 with a value of R2 = 0,9938. Furthermore, paracetamol without degradation was 90,40%, while paracetamol with degradation was 87,98%. It was concluded that there was a decrease in the levels of paracetamol treated with degradation, so it was stated that there was an indication of the effect of forced degradation by hydrolysis of paracetamol. The advice given by the researcher is to develop further research related to validation methods and degradation studies in determining the levels of paracetamol tablets.